"Tooth marker" to diagnose diabetes mellitus - Dipti Bhatnagar; N Gnanasundararn (Wolters Kluwer Medknow Publications, 2009)
During clinical examination of patients to diagnose oral diseases, it was observed that many patients had Cuspal destruction with saucer shaped cavity, ill defined pits and fissures with flattening of occlusal surface in the First permanent molars. The tooth is slightly yellowish in color. Many people who are having this tooth were diabetic. The tooth appeared as Attrition Pattern. A research has been carried out to find out whether this tooth has any relevance to diabetes mellitus. Incidence of attrition pattern among non diabetic, diabetic patients and Incidence of diabetes among attrition patients were carried out. Further gingival biopsies were taken to find out microangiopathy and PAS positive in vessels of connective tissue among diabetic, non diabetic and patients with attrition pattern. The observations of Research are correlated with one another and it was found that the attrition pattern have significant relation to diabetes. The use of attrition pattern as a marker to diagnose diabetes has been discussed.